DESAIN SISTEM PESANTREN DALAM MENINGKATKAN PERFORMA PENDIDIKAN ISLAM DI PP AL-HUSEN BANGKES KADUR PAMEKASAN - Khalik, Abd (Universitas Islam Madura, 2017)
Design management of educational boarding school in enhancing the value of education schools in Al-Husen have been done in some various ways: a) Holding change management model of education that is applied, b) Changes at the structure of personnel management, c) Organize the implementation and application refinement of educational programs, d) Conducting services repair and curriculum improvement, e) Conducting administrative system changes. The constraints faced in the implementation of educational management boarding schools are a) pattern of the management of the schools are still using a traditional system or old patterns such as administration disorderly, b) adopting a